Lithium use in childhood and adolescence, peripartum, and old age: an umbrella review - Delfina Janiri; Gaia Sampogna; Umberto Albert; Filippo Caraci; Giovanni Martinotti; Gianluca Serafini; Alfonso Tortorella; Alessandro Zuddas; Andrea Fiorillo; Gabriele Sani (International Journal of Bipolar Disorders, 2023)
Abstract Background Lithium is one of the most consistently effective treatment for mood disorders. However, patients may show a high level of heterogeneity in treatment response across the lifespan. In particular, the benefits of lithium use may vary in special clinical conditions. The aim of this study was to test this hypothesis by conducting an umbrella review on the efficacy and safety of lithium in childhood and adolescence, peripartum and old age. Methods We applied the Preferred Reporting Items for Systematic Reviews and Meta-analyses criteria (PRISMA) to identify systematic reviews/meta-analyses on the efficacy and/or safety of lithium in mood disorders in special clinical conditions: (i) childhood and adolescence; (ii) peripartum (pregnancy, postpartum and lactation); (iii) old age. The Risk of Bias Assessment Tool for Systematic Reviews (ROBIS) tool was used to assess the risk of bias. Overlap in primary studies across systematic reviews was calculated through the Corrected Covered Area (CCA). Results We included 20 independent studies, for a total of 8209 individuals treated with lithium. Regarding paediatric age, efficacy and safety results suggested that lithium may be superior to placebo in bipolar disorders (BD) and not associated with serious adverse events. Nevertheless, primary available data are very limited. Efficacy in paediatric major depressive disorder (MDD) is not clear. During peripartum, lithium use was superior to non-lithium in preventing mood episodes and it was associated with low risk of congenital anomalies and with normal child neurodevelopment. Regarding old age, limited evidence supported lithium as an effective treatment in BD and resistant MDD; low doses should be used in this population. Systematic reviews on paediatric age showed the lowest risk of bias (80% of the studies at low risk). The CCA range of included studies was 13–47%. Conclusions This umbrella review supports the use of lithium across the lifespan, including special clinical condition. Nevertheless, more studies with increased methodological homogeneity are needed.